2015
DOI: 10.1017/s0142716415000053
|View full text |Cite
|
Sign up to set email alerts
|

Reading skill and exposure to orthography influence speech production

Abstract: Orthographic experience during the acquisition of novel words may influence production processing in proficient readers. Previous work indicates interactivity among lexical, phonological, and articulatory processing; we hypothesized that experience with orthography can also influence phonological processing. Phonetic accuracy and articulatory stability were measured as adult, proficient readers repeated and read aloud nonwords, presented in auditory or written modalities and with variations in orthographic nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 66 publications
(90 reference statements)
2
27
0
Order By: Relevance
“…The notion of a role of orthography in spoken word production is not new though has received less attention than in spoken word recognition. Our findings are in line with prior studies that showed influences of orthography in production by comparing the performance of literate participants on different sets of words (e.g., Rastle et al, ; Saletta, Goffman, & Brentari, ). The originality of the present study regards the strong methodological design it offered: controlling for possible confounds of formal education and related experiences, and as much as possible of maturation and cognitive development (by comparing two matched populations equally deprived of early schooling, ex‐illiterate vs. illiterate), while dispensing the between‐item designs for testing literacy effects, necessary when all participants are readers.…”
Section: Discussionsupporting
confidence: 92%
“…The notion of a role of orthography in spoken word production is not new though has received less attention than in spoken word recognition. Our findings are in line with prior studies that showed influences of orthography in production by comparing the performance of literate participants on different sets of words (e.g., Rastle et al, ; Saletta, Goffman, & Brentari, ). The originality of the present study regards the strong methodological design it offered: controlling for possible confounds of formal education and related experiences, and as much as possible of maturation and cognitive development (by comparing two matched populations equally deprived of early schooling, ex‐illiterate vs. illiterate), while dispensing the between‐item designs for testing literacy effects, necessary when all participants are readers.…”
Section: Discussionsupporting
confidence: 92%
“…Fifty-two individuals participated in the study with 17 in the Adult-Typ group who ranged in age from 19 to 64 years old (M = 29.73; SD = 13.16); 17 in the child group, who ranged in age from 6.00 to 8.83 years old (M = 7.45; SD = 0.91); and 18 in the Adult-LP group, who ranged in age from 19 to 62 years old (M = 32.82; SD = 13.89). The individuals in the Adult-Typ group were drawn from a prior study of orthographic processing (Saletta et al, 2015). All participants were native speakers of English and demonstrated typical nonverbal reasoning and oral language.…”
Section: Methodsmentioning
confidence: 99%
“…The procedures were designed to evaluate the effects of modality and transparency on speech production (Saletta et al, 2015). Two measures-segmental accuracy and speech movement stability-were used to evaluate these effects.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations